Effect of simvastatin on expression of Interleukins 6 & 10 and Matrix Metalloproteinase: 9 when used as an intracanal medicament in teeth with symptomatic apical periodontitis-a triple blind randomized controlled trial - Nikhil Harikrishnan; Ravi Kumar Nesamani; S. Aysha Sherin; Kavitha Sanjeev; Mahalaxmi Sekar (Journal of Translational Medicine)
Abstract Background The objective of this prospective, triple-blind, randomized clinical controlled trial is to investigate and compare the expressions of interleukin-6 (IL-6), interleukin-10 (IL-10), and matrix metalloproteinase-9 (MMP-9) in the periapical tissues of teeth with symptomatic apical periodontitis following the placement of calcium hydroxide (Ca(OH)₂) and simvastatin as intracanal medicaments (ICM). Additionally, the study aims to evaluate pre-treatment and interappointment pain levels. This research could lead to improved treatment protocols for symptomatic apical periodontitis, enhancing patient comfort and outcomes. Methods The study adhered to CONSORT guidelines. A total of 34 patients aged 14 to 60 years with single-rooted teeth diagnosed with pulp necrosis and symptomatic apical periodontitis underwent root canal procedures. They were randomly divided into two groups based on the ICM used: Group I received Ca(OH)₂, while Group II received simvastatin. Tissue fluid samples were collected at three time points (T0, T1, T2) using paper points inserted into the periapical tissues immediately after access opening, after cleaning and shaping, and 7 days after ICM placement. The samples were stored at – 20 °C for analysis. Pain levels were recorded using the Heft Parker Visual Analogue Scale (HP-VAS) at various intervals. All samples underwent enzyme-linked immunosorbent assay (ELISA) to estimate IL-6, IL-10, and MMP-9 levels in pg/ml. Statistical analysis included the Mann–Whitney U test and Quade nonparametric ANCOVA for inter-group comparisons, while intra-group comparisons were performed using the Friedman test. Results Statistically significant differences were observed in IL-6 and MMP-9 levels within groups but not in IL-10 across time points (p < 0.05). In intergroup comparisons at T2, simvastatin showed significantly lower expressions of IL-6 and MMP-9 compared to Ca(OH)₂ (p < 0.05). IL-10 levels increased in both groups without significant differences. Pain scores were significantly lower following simvastatin treatment compared to Ca(OH)₂ (p < 0.05). Conclusions The expression of these biomarkers indicates that simvastatin is effective in reducing inflammation and pain in teeth with pulpal necrosis and symptomatic apical periodontitis when used as an intracanal medicament compared to Ca(OH)₂. Trail Registration: Clinical Trial Registry of India CTRI/2022/08/044749; Registered 18 August 2022 https://drive.google.com/file/d/17JXArM3qoqvTMiUa9ITMTQTGLEvsxpW_/view?usp=sharing